2011
DOI: 10.1007/s10198-011-0308-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of antipsychotic polypharmacy with health service cost: a register-based cost analysis

Abstract: The results demonstrate that antipsychotic co-prescribing is associated with increased use of health care services, even though no causal relations can be inferred from an observational study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 31 publications
3
19
1
Order By: Relevance
“…Also, Joukamaa 8 found an association between a higher number of antipsychotics at baseline and mortality after 17 years of follow up. Conversely, Baandrup 2 , in a population-based, nested, case-control study, found no relationship between APP and mortality and Tiihonen 87 , in a population-based cohort study, found even that long-term antipsychotics use was associated with lower mortality compared to no antipsychotic use (adjusted HR= 0.81, 95%CI: 0.77–0.84), and that APP was not more likely to produce increased mortality compared to perphenazine (adjusted HR= 1.08, 95%CI: 0.92–1.26). Notably and confirming prior findings, this study showed that clozapine was associated with significant lower risk of death by suicide, and all cause mortality compared to all other antipsychotics, whereas, at least over the medium-term follow-up in this study, no increased death from ischemic heart disease was observed.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, Joukamaa 8 found an association between a higher number of antipsychotics at baseline and mortality after 17 years of follow up. Conversely, Baandrup 2 , in a population-based, nested, case-control study, found no relationship between APP and mortality and Tiihonen 87 , in a population-based cohort study, found even that long-term antipsychotics use was associated with lower mortality compared to no antipsychotic use (adjusted HR= 0.81, 95%CI: 0.77–0.84), and that APP was not more likely to produce increased mortality compared to perphenazine (adjusted HR= 1.08, 95%CI: 0.92–1.26). Notably and confirming prior findings, this study showed that clozapine was associated with significant lower risk of death by suicide, and all cause mortality compared to all other antipsychotics, whereas, at least over the medium-term follow-up in this study, no increased death from ischemic heart disease was observed.…”
Section: Resultsmentioning
confidence: 97%
“…The use of two or more antipsychotics, also called antipsychotic polypharmacy (APP), has attracted clinical, research and stakeholder interest 1, 2 . Reasons for this include: 1) APP is a fairly commonly used pharmacological practice in the treatment of psychiatric patients, especially those with psychotic disorders 3 , and the percentage of schizophrenia patients receiving APP has increased during the last decade 4, 5 ; 2) evidence for its efficacy and effectiveness is relatively slim or contradictory 6, 7 ; and 3) concerns have been raised about the potential for increased adverse effects, problems with patient safety, and increased healthcare cost 2, 8 .…”
Section: Introductionmentioning
confidence: 99%
“…2022,96,122125 For example, in an analysis of an outpatient Medicaid population, APP was the most expensive form of SGA use, costing up to 3 times more per patient than mono-therapy. 14 In another study of 836 patients treated in New Hampshire between 1995 and 1999, the increase in the prevalence of APP from 6% to 24% resulted in an average increased medication cost of $400/mo per patient.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the potential influence of individuals with extreme consumption of health care resources (outliers: more than 3 standard deviations from the mean) [28] All analyses were conducted using SAS 9.4 software and a p value < 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%